The Effect of Brand Innovativeness and Brand Love on WOM Through Customer Trust for Shopee Users in Yogyakarta - Domi Kirana; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami (Journal La Sociale, 2023)
The people of Yogyakarta are satisfied when making purchases at Shopee because Shopee has been able to meet or even exceed their expectations. The customer trust that consumers have towards Shopee in the Yogyakarta area can of course influence WOM. E-Wom was formed due to positive conveyed by previous customers via social media, feelings gained through experiences that have been felt when using services or services provided by service providers or those providing services. The population in this study were all students using Shopee in Yogyakarta. The sampling technique was purposive sampling with a sample size of 120 people. Data collection was carried out using questionnaires and data analysis in this research used Smart PLS. The influence of brand innovativeness and brand love on trust is stated to be positive and significant because the original sample value obtained is positive and the p value is <0.05. The influence of brand innovativeness and brand love on loyalty is stated to be positive and significant because the original sample value obtained is positive and the p value is <0.05. Customer trust has no effect on loyalty. Brand innovativeness has no effect on WOM through customer trust among Shopee users in Yogyakarta. Brand love for WOM through customer trust love for Shopee users in Yogyakarta.